Bi-allelic variants in COQ8B, a gene involved in the biosynthesis of coenzyme Q10, lead to non-syndromic retinitis pigmentosa - Iglesias-Romero, Ana Belén (2024)
Copyright © 2024 The Authors. Published by Elsevier Inc. All rights reserved.